Digital Self-Efficacy and Organizational Support: a Pathway to Digital Resilience and Performance - Vellen Wibowo (Green Publisher Indonesia, 2026)
This study aims to examine the role of digital self-efficacy in predicting digital resilience, with perceived organizational support as a mediator between digital resilience and employees’ performance in technology-based companies. This analysis seeks to uncover individual and organizational factors that foster adaptability and productive growth in the digital era. The study was conducted using a quantitative survey design with a cross-sectional approach among digital-intensive workplaces in the technology, finance, education, and e-commerce sectors. A total of more than 320 participants were recruited through online stratified random sampling. A 5-point Likert scale was used to measure responses, and Structural Equation Modeling (SEM) was employed to examine direct, indirect, and moderating effects among the study constructs. The results indicate that digital self-efficacy is significantly and positively related to digital resilience, which in turn influences employee performance. Perceived organizational support serves as a moderator in the relationship between resilience and performance, highlighting the interdependence between individual digital competencies and organizational support systems. This study contributes to the theoretical foundation of digital resilience by integrating both individual and organizational perspectives. The findings suggest that organizations should focus on enhancing employees’ digital self-efficacy, fostering supportive work climates, and promoting lifelong learning. Such initiatives are vital in building resilience, unlocking creativity, and sustaining long-term performance amid ongoing digital disruption.